Perancangan Tempat Sampah Pintar Berbasis Arduino Uno - Fa`iq Khotibul Umam; Nuris Dwi Setiawan; Danang Danang; Mufadhol Mufadhol (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
The lack of awareness from Resto visitors in the process of disposing of garbage in its place makes the environment around the Resto polluted at least the awareness of Resto visitors to dispose of garbage in its place is still low. The purpose of this research is to create an automation system for the trash can. The problem that arises for Resto S2 is the lack of effectiveness, especially in the tissue waste section, one of the solutions that can be done for these problems, namely by designing a device in the form of a smart trash can that can open and close automatically, so that Resto visitors do not need to make direct contact with the trash can. Researchers aim to realize the design of the tool, as for the method carried out in this study is to implement the design of a smart trash can in the form of a box that has an input in the form of an ultrasonic sensor, and an output in the form of a servo motor. The results of input and output testing show that the ultrasonic sensor can detect movement in front of the trash can and the servo motor can move the trash can cover, so it can be concluded that the smart trash can work system as a whole can function properly in accordance with the design that has been made.